2021
DOI: 10.33902/jpr.2021371747
|View full text |Cite
|
Sign up to set email alerts
|

An inquiry into EFL teachers beliefs concerning effective teaching, student learning and development

Abstract: How teaching could be conducted effectively and consequently student learning could be enhanced presumably vary from teacher to teacher, arising from a variety of such factors as the conditions in the workplace, teachers' year of teaching experience and their prior schooling experiences. In this regard, English-as-a-foreign-language (EFL) teachers' (EFLTs) beliefs about quality teaching leading to facilitated student learning are also highly likely to be divergent. This survey research aims to add to the growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…This result may be because of the accumulative teaching experiences that EFL teachers acquire through their working years, in which they are more exposed to different teaching practices and curricula of English language skills. The current result accords with Kosar and Dolapçıoğlu (2021) study, which indicated significant differences in EFL teachers' beliefs concerning teaching practices attributed to teaching experience.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result may be because of the accumulative teaching experiences that EFL teachers acquire through their working years, in which they are more exposed to different teaching practices and curricula of English language skills. The current result accords with Kosar and Dolapçıoğlu (2021) study, which indicated significant differences in EFL teachers' beliefs concerning teaching practices attributed to teaching experience.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Khalil and Semono-Eke (2020) indicated that English language instructors preferred combining other teaching techniques with communicative language teaching. Further, Kosar and Dolapçıoğlu (2021) highlighted teachers' use of interactively learning activities to maximize their students' English learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phenomenographic arguments are primarily focused on the teacher-centered and student-centered spectrum of the same scale as a horizontal aspect to document teachers’ or teacher educators’ conceptions of learning, teaching, or pedagogy (e.g., Brody & Hadar, 2011; Buaraphan, 2011; Kosar, 2021; López-Íñiguez & Pozo 2014; Soysal & Radmard, 2018; Wall, 2016). However, in the current state of teacher preparation theories, the mentioned horizontal aspect would be oversimplified or too commonsensical.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In developing learning methods or techniques, various criteria for quality methods or techniques must be considered. According to Dolapçıoğlu and Koşar[37] there are four criteria for a good learning method or technique, namely: i) It can arouse students' curiosity; ii) It can generate positive optimism in students; iii) It can foster student creativity;…”
mentioning
confidence: 99%